Nursing Behaviour in Alpacas: Parallels in the Andes and Central Europe, and a Rare Allonursing Occurrence - Marešová, Jana; Kokošková, Tersia; Tichá, Eliška; Fedorova, Tamara (Animals, 2025)
Understanding maternal behaviour is essential for good animal husbandry; yet, little scientific information currently exists regarding nursing behaviour of alpacas (Vicugna pacos). Moreover, allonursing (the nursing of non-filial offspring) has only been documented in captive non-domesticated guanacos. This study aimed to (1) describe the nursing behaviour of alpacas within traditional husbandry systems in their place of origin, and in foreign conditions, and to (2) investigate the occurrence of allonursing in alpacas. A total of 1899 nursing bouts were observed in the Andes and Central Europe. Additionally, 102 Andean farmers were asked if they observed allonursing in their herds. Nursing behaviour was similar at both locations, with most of the nursing bouts initiated by crias and terminated by dams. However, several significant differences between localities were noted, such as the less frequent sniffing of crias by Andean dams. Crias' age and sex did not affect the percentage of nursing bouts initiated or terminated by the dams. Rare cases of allonursing were recorded in Central Europe (n = 5), and 18.6% of surveyed Andean farmers reported allonursing in their herds. This study provides insight into alpaca nursing and allonursing behaviour, which may contribute towards their management both in their place of origin and farther.
Keywords: Vicugna pacos; allosuckling; nursing duration; nursing of crias; maternal behaviour